Strategi Komunikasi Satuan Lalu Lintas Polres Blitar Kota Melalui Program Save Our Student dalam Upaya Menekan Jumlah Pelanggaran Lalu Lintas Pada Pelajar - Meita Anisa Saputra* (Universitas Airlangga, 2018)
Data from the City Blitar City Police Unit in 2016, as many as 1,799 or 15.9% of students committed traffic violations, from January to March 2017 as many as 438 or 11.3% of students committed traffic violations. In addition to violations, 25 or 15.1% of traffic accidents involving students occurred. The accident caused 68 students to become victims. In 2017 January to March as many as 6 or 12.5% students were involved in traffic accidents. The accident caused 21 students to become victims. According to the data, it can be seen that the number of traffic violations in Blitar City is dominated by students, both students of junior high schools, senior high schools or vocational high schools. Then the Save Our Student (SOS) program was implemented to reduce the number of traffic offenses for students. The Save Our Student (SOS) Program is a Satlantas Polres Blitar Kota program in collaboration with schools, both Middle School (SMP), Senior High School (SMA) or Vocational High School (SMK) in Blitar City. The Save Our Student (SOS) Program is a program based on Law Number 22 Year 2009 concerning Road Traffic and Transport and the Safety riding program. The Save Our Student (SOS) program is not just a momentary program, but an ongoing program in an effort to reduce the number of traffic violations on students in the City of Blitar. The Blitar City Police Traffic Unit Police in implementing the Save Our Student (SOS) Program needs a communication strategy, where the success rate of a goal will be achieved along with how the communication strategy is carried out in implementing the Save Our Student (SOS) Program. The purpose of the program, which is to reduce the number of traffic violations among students and prevent traffic accidents with fatality fatalities will be achieved.